1995
DOI: 10.1046/j.1471-4159.1995.65052209.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Administration Attenuates Cognitive but Not Neurobehavioral Motor Dysfunction or Hippocampal Cell Loss Following Fluid‐Percussion Brain Injury in Rats

Abstract: Lateral fluid‐percussion brain injury in rats results in cognitive deficits, motor dysfunction, and selective hippocampal cell loss. Neurotrophic factors have been shown to have potential therapeutic applications in neurodegenerative diseases, and nerve growth factor (NGF) has been shown to be neuroprotective in models of excitotoxicity. This study evaluated the neuroprotective efficacy of intracerebral NGF infusion after traumatic brain injury. Male Sprague‐Dawley rats received lateral fluid‐percussion brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 38 publications
(69 reference statements)
1
22
1
Order By: Relevance
“…The test is commonly used to evaluate the effect of TBI and potential treatment strategies. Previous studies using growth factor treatment after TBI have shown beneficial effects on MWM performance (Lu et al, 2005;Sinson et al, 1995). The positive effect of EGF infusion and VEGF scaffold that we found in While we found a significant effect of the trauma on MWM performance day 36-39 after injury, we could not see any effect of the treatment at this time point.…”
Section: Discussioncontrasting
confidence: 58%
“…The test is commonly used to evaluate the effect of TBI and potential treatment strategies. Previous studies using growth factor treatment after TBI have shown beneficial effects on MWM performance (Lu et al, 2005;Sinson et al, 1995). The positive effect of EGF infusion and VEGF scaffold that we found in While we found a significant effect of the trauma on MWM performance day 36-39 after injury, we could not see any effect of the treatment at this time point.…”
Section: Discussioncontrasting
confidence: 58%
“…The continuous presence of NGF infused for at least 4 weeks appears to be required to prevent degeneration of cholinergic neurons after fimbria-fornix transection [112]. Following lateral FP brain injury in rats, intracerebral NGF infusion in the acute phase beginning at 24 h after injury and lasting until the time of sacrifice (72 h, 1 week, 2 weeks) improved memory (when evaluated at 1 and 2 weeks after injury) but not motor function or hippocampal cell loss [113]. Intraparenchymal NGF infusion for 2 weeks after lateral FP brain injury in rats also reduced memory deficits up to 4 weeks after injury, and concomitantly decreased cholinergic neuronal loss and apoptotic cell death in the medial septum [97], suggesting that the behavioral improvements persist after cessation of NGF administration and that the beneficial effects of NGF may be related to its ability to attenuate traumatically induced apoptotic cell death.…”
Section: Therapeutic Administration Of Ngfmentioning
confidence: 99%
“…The BDNF infusions reduce vestibular deficits, increase neuronal metabolism, and prevent degeneration of nigral neurons (Altar et al, 1994;Volpe et al, 1998). Intraventricular infusion of nerve growth factor (NGF) has been shown to promote the survival of cholinergic neurons, improve cognitive function, and reduce apoptosis in various rat models of traumatic brain injury (Dixon et al, 1997;Sinson et al, 1995Sinson et al, , 1997. The infusion of basic fibroblast growth factor (bFGF) following brain trauma also helped restore cognitive function (McDermott et al, 1997).…”
Section: Pump-catheter Systemsmentioning
confidence: 99%